“Behind every street boy there is an unemployed parent” . Social organizations and trade unions fighting for a decent childhood (1983 - 2001) - Shabel, Paula (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2017)
The aim of this paper is to analyze the relationship between the social organizations that work with the childhood of the poor and the trade unions during 1983 - 2001. We have made a bibliographic and journalistic revision to study the period and then crossed it with interviews made to the people involved in these processes at that time, as well as with audiovisual material produces by them and their institutions. As a result, we established a linkage between organizations and trade unions that strengthen their claims and bolster their legitimacy, enlarging the concept of class and childhood.